Green Marketing as a Vital Approach to Support the Social Responsibility in Enterprises - بن منصور ليليا; عجالي دلال (Finance and Business Economies Review, 2019)
This study aims at highlighting the role played by green marketing in supporting the social responsibility of economic enterprises as they have common objectives that serve the interests of societies. The descriptive approach was used to inform the theoretical aspect of corporate social responsibility, green marketing and analysis to highlight the effect of green marketing on supporting the corporate social responsibility. The study concluded that green marketing enterprises can effectively support their social responsibility. As it found the hypothesis and considered green marketing as a vital approach to support social responsibility in the enterprises, to the green marketing mix supports corporate social responsibility through all of its elements (green product, promote, pricing and green distribution).